May intraoperative detection of stereotactically inserted intracerebral electrodes increase precision of resective epilepsy surgery?. (November 2021) - Belohlavkova, Anezka; Jahodova, Alena; Kudr, Martin; Benova, Barbora; Ebel, Matyas; Liby, Petr; Taborsky, Jakub; Jezdik, Petr; Janca, Radek; Kyncl, Martin; Tichy, Michal; Krsek, Pavel
Abstract: Object: Epilepsy surgery is an effective treatment for selected patients with focal intractable epilepsy. Complete removal of the epileptogenic zone significantly increases the chances for postoperative seizure-freedom. In complex surgical candidates, delineation of the epileptogenic zone requires a long-term invasive video/EEG from intracranial electrodes. It is especially challenging to achieve a complete resection in deep brain structures such as opercular-insular cortex. We report a novel approach utilizing intraoperative visual detection of stereotactically implanted depth electrodes to inform and guide the extent of surgical resection. Methods: We retrospectively reviewed data of pediatric patients operated in Motol Epilepsy Center between October 2010 and June 2020 who underwent resections guided by intraoperative visual detection of depth electrodes following SEEG. The outcome in terms of seizure- and AED-freedom was assessed individually in each patient. Results: Nineteen patients (age at surgery 2.9–18.6 years, median 13 years) were included in the study. The epileptogenic zone involved opercular-insular cortex in eighteen patients. The intraoperative detection of the electrodes was successful in seventeen patients and the surgery was regarded complete in sixteen. Thirteen patients were seizure-free at final follow-up including six drug-free cases. The successful intraoperative detection of the electrodes was associated with favorable outcome in terms of achieving complete resection and seizure-freedom in most cases. On the contrary, the patients in whom the procedure failed had poor postsurgical outcome. Conclusion: The reported technique helps to achieve the complete resection in challenging patients with the epileptogenic zone in deep brain structures. Highlights: Visual detection of SEEG electrodes facilitates orientation during the surgery. Suitable in patients with normal finding on brain MRI. Well applicable and beneficial especially in operculo-insular region.